Symptom Assessment in Knee Osteoarthritis Needs to Account for Physical Activity Level - Lo, Grace H. (Arthritis Rheumatol, 2015)
OBJECTIVE: Pain is not always correlated with radiographic osteoarthritis (OA) severity possibly because people modify activities to manage symptoms. Measures of symptoms that consider pain in the context of activity level may therefore provide greater discrimination than pain alone. Our objective was to compare discrimination of a measure of pain alone with combined measures of pain relative to physical activity across radiographic OA levels. METHODS: This is a cross-sectional study of the Osteoarthritis Initiative accelerometer substudy, including those with and without knee OA. Two composite pain and activity knee symptom (PAKS) scores were calculated as Western Ontario and McMaster (WOMAC) Universities Osteoarthritis Pain Scale plus one divided by physical activity measures (step and activity counts). Symptom score discrimination across Kellgren and Lawrence (KL) grades were evaluated using histograms and quantile regression. RESULTS: 1806 participants, mean age 65.1 (9.1) years, mean BMI 28.4 (4.8) kg/m(2), and 55.6% female, were included. WOMAC, but not PAKS scores, exhibited a floor effect. Adjusted median WOMAC by KL grades 0 – 4 were 0, 0, 1, 1, and 3 respectively. Median PAKS1 and PAKS2 were 24.9, 26.0, 32.4, 46.1, 97.9, and 7.2, 7.2, 9.2, 12.9, 23.8, respectively. PAKS scores had more statistically significant comparisons between KL grades compared with WOMAC. CONCLUSIONS: Symptom assessments incorporating pain and physical activity did not exhibit a floor effect and were better able to discriminate radiographic severity than pain alone, particularly in milder disease. Pain in the context of physical activity level should be used to assess knee OA symptoms.